FISCAL DECENTRALISATION IN THE FIELD OF INDUSTRIAL RELATIONS WITHIN THE FRAMEWORK OF HARMONISATION OF NATIONAL FISCAL POLICY - Hendro Prabowo (Justitia et Pax, 2026)
The primary objective of regional autonomy is to achieve equitable management of natural and human resources, ultimately enhancing the well-being of individuals. Regional autonomy and decentralization are inseparable. The labour sector is separated into various areas of responsibility, including industrial relations issues. This particular area is further subdivided into matters concerning the central government, province governments, and district or municipal regional governments. Implementing regional autonomy to govern regional finances based on their own capacity is a crucial aspect of fiscal decentralization. Fiscal decentralization is dependent on the synchronisation of fiscal policies at both the national and regional levels. In order to sustain economic progress and prosperity, it is imperative to establish a harmonious collaboration between the central authority and the various areas. This study will examine two specific issues: First, if the arrangements for the division of affairs in the field of industrial relations have implemented fiscal decentralization. Second, the alignment of fiscal decentralization with national fiscal policy is crucial in implementing regional autonomy in the field of industrial relations. This legal document employs normative legal research with a legislative approach, focusing on state finances, employment, fiscal policy, regional government, and various government policy documents, including KEM PPKF. This study's findings indicate that integrating government issues into the labour sector, namely industrial relations, within the context of fiscal decentralization and decentralization, is consistent with national budgetary strategy. This alignment is evident through numerous regulations pertaining to central and regional financial relations, employment regulations, regional financial management regulations, and guidelines for preparing the APBD.